(untitled) (Global Journal of Human-Social Science, 2019)
The article analyses an essence character and forms of the volunteer s organizations participation in the struggle with the accidents i e with critical situations hereafter the CS generated by the outside and inside forces and contradictions paying special attention to the socially-constructed CS The authors set forth the foundations of the theory of an emergence and development of the CS defines their main archetypes and offers a differentiation of their three phases of development initial the CS as such and the mitigation of their immediate and far-reaching natural social and technological consequences A necessity of the volunteers and individual civil rescuers participation in the various phases of the CS and in coping with their social and other consequences is substantiated A brief history of this type of civic organizations in Russia of the XX and at the beginning of the XXI is set forth a necessity of differentiation of functions of a state i e its rescue forces and civil society volunteers organization is explained The article gives a preliminary estimation of an efficiency of the use of various methods of the CS studies and their consequences The authors offer a preliminary typology of the volunteers organizations with a focus on their universal and international character The article concluded with the statement that the volunteers movement is not only a mean to help to the nature and people in a calamity but it s an indispensable mean for giving to its participants a feeling of an intellectual and socially active persons